AN ANALYSIS ON ONLINE CRIMINAL CASE HEARINGS: CAN JUSTICE BE SERVED ONLINE? - Simandjuntak, Marcella Elwina; Saraswati, Rika; Soerjowinoto, Petrus; Boputra, Emanuel (Masalah-Masalah Hukum, 2024)
This paper examines the accountability of online criminal case adjudication in Indonesia during the COVID-19 pandemic. Although normal court trials have resumed, the judiciary must prepare for the integration of online trials to improve efficiency and case management. This empirical study employs qualitative methods, collecting data through interviews with judges, prosecutors, and written interviews with lawyers, along with questionnaires. Conducted in three district courts in Central Java, it also incorporates secondary data from legal statutes and literature. Most judges, prosecutors, and attorneys found online trials accountable, with outcomes comparable to in-person hearings. However, challenges persist, such as administrative gaps, and technical disruptions. The study urges legislative action to establish procedural norms for online trials and recommends improving court decisions' quality and quantity to ensure justice.